2017
DOI: 10.11648/j.ajp.20170306.12
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Acute Diarrheal Disease Among Under-Five Children in Pawi Hospital, Northwest Ethiopia, 2013/14

Abstract: Background: Diarrhea is one of the leading causes of morbidity and mortality among under-five children nationally and globally. This study identified determinants of acute diarrheal disease among under-five children using hierarchical logistic regression. Objective: This study was conducted to identify determinants for hospitalization of children with acute diarrhea in Pawi Hospital, Benishangul Gumuz Region, Northwest Ethiopia, 2013/14. Methods: A hospital-based case-control study was performed on 148 cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 12 publications
(13 reference statements)
6
18
0
Order By: Relevance
“…The result of this study was similar to the study findings conducted in Ethiopia Harar Town, Medebay Zana District, and Pawi Hospital, Northwest Ethiopia (13,19,26). The fact that parents/legal guardians are the most food handlers of the family and the main childcare providers; hence, the possibility of diarrheal diseases among children with parents/legal guardians who had diarrheal diseases is a usual event.…”
Section: Hand Washingsupporting
confidence: 89%
See 2 more Smart Citations
“…The result of this study was similar to the study findings conducted in Ethiopia Harar Town, Medebay Zana District, and Pawi Hospital, Northwest Ethiopia (13,19,26). The fact that parents/legal guardians are the most food handlers of the family and the main childcare providers; hence, the possibility of diarrheal diseases among children with parents/legal guardians who had diarrheal diseases is a usual event.…”
Section: Hand Washingsupporting
confidence: 89%
“…Town, Medebay Zana District, and Pawi Hospital, Northwest Ethiopia (13,19,26 The result of this study also revealed that households who improperly utilized latrine were 2 times more likely at risk to develop diarrheal diseases among under-five children compared to households that utilized latrine properly. This result was comparable with the study finding reported from West Gojjam of Ethiopia (12) and Kawangware Slum in Nairobi County, Kenya (27).…”
Section: Socio-demographic Characteristics Of Study Participantsmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, considerable gap exists between the level of knowledge on the one hand and the levels of attitude and practice among mothers in Debarq. More or less similar gap in hand washing knowledge and practice prevails in other places in Ethiopia [35, 51, 52]. Not only does the disparity between the food safety related knowledge and practice exist in Ethiopia but it is a phenomenon in other developing countries as well [53–57].…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding, particularly when exclusive and prolonged, protects against severe morbidities such as diarrhea and respiratory infections [4]. Various studies documented that bottle-feeding is associated with child morbidity (e.g., diarrhea, respiratory infection, and allergies) and mortality [9], [10], [43], [44], [45], [46]. For example, in Sudan, bottle-fed children were at high risk of malnutrition and hospitalization due to infectious causes as 83.3% of hospitalized children used bottle feeding [9].…”
Section: Discussionmentioning
confidence: 99%